Reappraising the Diagnostic Accuracy of Post-Treatment Whole-Body Scans for Differentiated Thyroid Carcinoma - Nava, Carla Fernanda; Scheffel, Rafael Selbach; Zanella, André Borsatto; Zelmanovitz, Flavio; Maia, Ana Luiza; Dora, Jose Miguel (Hormone and Metabolic Research, 2020)
Initial treatment for differentiated thyroid carcinoma (DTC) often consists of surgery and the administration of radioiodine. In this context, post-treatment Whole-Body Scans (ptWBS) are currently recommended, but data on its diagnostic accuracy are rare. The aim of the study was to evaluate the performance of ptWBS for distant metastasis in DTC patients. We included DTC patients who received radioiodine and underwent ptWBS between 2009–2015. The medical data were independently reviewed by two specialists to evaluate the concordance of positive distant ptWBS uptake and distant metastasis documented by imaging exams (gold standard). We studied 268 DTC patients. The mean age was 46±16 years (82% women), and papillary thyroid carcinoma was diagnosed in 87% of the patients. The median tumor size was 2.7 cm, 40% had lymph node involvement, and 11% had distant metastasis. Twenty-eight patients (10%) had distant ptWBS uptake, and nine of them (32%) were false-positives. In addition, nine false-negative ptWBS uptakes were identified. The overall performance of ptWBS showed 68% sensitivity and 96% specificity with significantly different performance according to the American Thyroid Association (ATA) risk groups. While the ptWBS performance for ATA low-intermediate-risk showed 29% sensitivity, 97% specificity, and Kappa of 0.19, the ATA high-risk group ptWBS displayed high sensitivity (82%), specificity (100%), and good agreement (Kappa 0.74). ptWBS is useful for a subgroup of ATA high-risk DTC patients. The overall poor performance of ptWBS suggests that it should be reconsidered for routine use in ATA at low to intermediate risk: the exam has little value to this subgroup.
Keywords: differentiated thyroid carcinoma; whole-body scan; radioiodine; prognosis; false-positive